Functional regions as a platform to define integrated transport system zones: The use of population flows data. (July 2022) - Kraft, Stanislav; Halás, Marián; Klapka, Pavel; Blažek, Vojtěch
Abstract: The rapid expansion of cars as the main transport mode over the last few decades has caused many negative effects mainly in urban areas. Many countries across the world thus want to attract passengers back to public transport. One of the most important and useful tools is supporting public transport by creating integrated transport systems (ITS). ITS represent innovative solution for organising urban and regional public transport. ITS are based on the integration of individual transport modes into one interconnected and coordinated system. However, the key question is how they are spatially defined and how they are organised internally. This is a relatively complicated issue as natural population flows, tariff systems, as well as the specifics of the transport infrastructure of the area, must be reflected. The main aim of the article is to propose the optimal delimitation and internal structure of the integrated transport system in the South Bohemian Region of the Czech Republic. To design the optimal delimitation, we use an innovative method based on utilizing location data from mobile phones, which reliably reflect the population flows. To delimitate the zones of a new integrated transport system we use the CURDS regionalisation algorithm and Smart's interaction measure. We found out substantial disproportion between the current organisation of the public transport system and regular population flows based on mobile positioning data. We suggest adjusting and developing a new integrated transport system which will reflect the current organisation of regular population flows. Finally, we test four versions of micro-regions as a sophisticated basis to define and internally structure the new ITS in the South Bohemian Region. Highlights: We use an innovative approach to delimitate and design the transport integrated system of public transport. Our approach is based on mobile positioning data as a useful tool to analyse regular population flows within the area. We have delimited four versions of ITS zones. The most suitable is the version D with 58 self-contained micro-regions. We suggest using the resulting micro-regions as a sophisticated platform for developing new ITS in the research area.